1989
DOI: 10.1104/pp.89.3.893
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Content and Activity of Sucrose Metabolism Enzymes in Milled Rice Grain

Abstract: Most rice (Oryza sativa L.) culfivars grown in the United States were selected for endosperm starch properties and not soluble sugar content. The minor pool of soluble sugar may affect the qualities of rice as a food. Some cultivar variation in soluble sugar content was detected in milled grain, essentially the starchy endosperm, of long grain varieties. Milled grain of cultivars Lemont and Texmati had a soluble sugar content of 0.21 and 0.35% (w/w), respectively, on a fresh weight basis. The dorsal portion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 17 publications
1
24
0
2
Order By: Relevance
“…48 Differences in starch granule size also influence starch functionality, 49,50 and grain sugars could increase due to stress-induced starch breakdown and may influence taste. 51 Here we found no difference in reducing sugar content (Table 3). Interestingly, we found that the Seedling EC4 and the Anthesis EC2 treatments increased the percentage of starch in the rice flour (Table 3) as well as in each caryopsis (Supporting Information Table S1).…”
Section: ■ Results and Discussionmentioning
confidence: 52%
“…48 Differences in starch granule size also influence starch functionality, 49,50 and grain sugars could increase due to stress-induced starch breakdown and may influence taste. 51 Here we found no difference in reducing sugar content (Table 3). Interestingly, we found that the Seedling EC4 and the Anthesis EC2 treatments increased the percentage of starch in the rice flour (Table 3) as well as in each caryopsis (Supporting Information Table S1).…”
Section: ■ Results and Discussionmentioning
confidence: 52%
“…It is becoming increasingly clear that SPS may play an important role in sucrose accumulation in sink tissues (3,8,17). We hope that future research will reveal to what extent fruit SPS may be involved in carbohydrate accumulation and sweetening of species other than muskmelon.…”
Section: Green-fleshed Muskmelonsmentioning
confidence: 99%
“…As rice is a non‐natural accumulator of glycine betaine, the role of choline is restricted to phospholipid biosynthesis. Endosperm, the storage tissue of the mature cereal grain, is chiefly composed of starch and a minor amount of soluble sugars such as glucose, fructose, sucrose, etc . The soluble sugar content in rice is known to vary between the cultivars .…”
Section: Resultsmentioning
confidence: 99%
“…Endosperm, the storage tissue of the mature cereal grain, is chiefly composed of starch and a minor amount of soluble sugars such as glucose, fructose, sucrose, etc. 20,21 The soluble sugar content in rice is known to vary between the cultivars. 22 Carbohydrates are mainly transported in the form of sucrose in the plant system through the phloem.…”
Section: Distribution Of Choline and Sugar Moleculesmentioning
confidence: 99%